Study of the Strength Characteristics of Soil Processed with Fly Ash and Recron 3s (International Journal of Innovative Research in Engineering & Management, 2022)
The main focus of this research was to  enhance the strength of soil & to get an optimum amount of  soil- fly-ash –Recon 3s mix. The target of study was to  extend the strength of clayey soil using ash &Recron3s. As  we all know ash act as a cement material & Recon 3s act as  a reinforcing material. As clay shows high shrinkage, swell  characteristics & low bearing capacity. There is a necessity  to enhance the strength characteristics. Therefore the main  focus of this research was to extend the strength  characteristics of soil. The tests performed in laboratory was  Pyconometer test for relative density casagrande’s test for  liquid limit, plastic limit test, Standard proctor test for  determination of OMC & MDD, unconfined compression  test & Direct shear test. Proportional of the recon 3s used was  0.2, 0.4, 0.6, 0.8 & 1.0 try to proportional of ash was 10,  15,20,30,40 & 50%. The ash was optimized at 15% & UCS  value for virgin soil was 215.6KN/m2& by adding ash in  numerous proportions i.e., 10, 15, 20,30,40,50. The UCS  values were 409.10, 460.1, 378.7, 345.2, 242.01 & 234.06 in  KN/m2 that the maximum was at 15% fly ash. After adding  Recron3s in several proportions i.e., 0.2, 0.4, 0.6, 0.8 & 1.0  %. The UCS values were 512.46, 566.49, 625.23, 672.1 &  654.35 in KN/m2 for 1 week curing. Therefore, the  maximum was at 0.8% & for two weeks curing UCS values  was 587.085, 625.23, 676.81, 710.2 & 672 in KN/m2 &  again was maximum for 0.8%. The results of direct shear test  for virgin soil was - cohesion intercept 24.6 KN/m2 & angle  of shearing resistance 19.20 & was increased by adding ash  & Recron3s at 15% ash & 0.8% Recron3s it had been 62.2  KN/m2 & 29.10.From this study it absolutely was concluded  ash works as a cementing material & Recron3s as a  reinforcing material & provides strength to the soil in  addition as fly ash .the most effective proportion obtained  was; 84.2% soil – 15% ash – 0.8% recon 3s. Also, the tactic  utilized in this research was randomly distributed  fiber reinforcement soil also turned as RDFS. Also, from  Proctor test it had been found that OMC increases & MDD  decreases with increase in fly ash & recon 3s.
Keywords: Soil; Recron-3S; Fly Ash; Stabilization; Fiber